Sustainable development as a conceptual basis for the restoration of territories in the post-war economy of Ukraine - Martynovych, Nataliia Oleksandrivna; Boichenko, Elina Borysivna (The University of Technology in Katowice Press, 2023)
The restoration of Ukraine is not a return to the pre–war state, but full development and integration into the European community based on sustainable development and considering the European Green course. Therefore, the purpose of the article is to develop conceptual provisions for the restoration of territories in the post-war economy of Ukraine based on sustainable development. The theoretical basis was the scientific works of domestic and foreign authors, certain provisions of the regulatory framework- legal acts such as the law of Ukraine "on amendments to certain legislative acts of Ukraine concerning the principles of State Regional Policy and the policy of restoration of Regions and territories", the resolution of the Cabinet of Ministers of Ukraine "on approval of the procedure for development, public discussion, coordination of programs for the comprehensive restoration of the region, the territory of the territorial community (it’s part) and amendments to them", the Order of the Cabinet of ministers of Ukraine "issues of data collection for monitoring the implementation of Sustainable Development Goals". The article proposes the concept of conversion of restoration territories, as well as develops sets of indicators. The author's approach expands the theoretical and methodological basis and allows you to distribute regions considering the degree of compliance of the level of human life expectancy, the level of well-being and development of each member of society achieved by the national economy at a certain point in time.

Відновлення України – це не повернення до довоєнного стану, а повноцінний розвиток та інтегрування до Європейського співтовариства на основі сталого розвитку та з урахуванням Європейського зеленого курсу. Відтак мета статті полягає у розробці концептуальних положень відновлення територій в післявоєнній економіці України на засадах сталого розвитку. Теоретичним базисом послужили наукові праці вітчизняних та зарубіжних авторів, окремі положення нормативно- правових актів, таких як: Закон України «Про внесення змін до деяких законодавчих актів України щодо засад державної регіональної політики та політики відновлення регіонів і територій», Постанова Кабінету Міністрів України «Про затвердження Порядку розроблення, проведення громадського обговорення, погодження програм комплексного відновлення області, території територіальної громади (її частини) та внесення змін до них», Розпорядження Кабінету Міністрів України «Питання збору даних для моніторингу реалізації цілей сталого розвитку». В статті запропоновано концепцією конверсії територій, а також розроблено комплекси показників. Авторський підхід розширює теоретико-методичний базис та дозволяє розподілити регіони з огляду на ступінь відповідності рівня тривалості життя людини, рівня добробуту та розвитку кожного члена суспільства, досягнутого національною економікою на певний момент часу.
Keywords: sustainable development; restoration of territories; post-war economy; assessment of territory restoration; стійкий розвиток; відновлення територій; післявоєнна економіка; оцінка відновлення територій